Firm Transparency and Employee-Oriented Corporate Social Performance. New Evidence from European Listed Firms - Garsaa, Aziza; Paulet, Elisabeth (Management international / International Management / Gestiòn Internacional, 2022)
This research aims to analyse the link between firm transparency, measured by the quality of environmental, social, and governance (ESG) disclosure, and employee-oriented corporate social performance (CSP). A panel data ordered logit model is estimated using a sample of 280 multinational manufacturing firms listed in the European capital market during the 2010–2017 period. Overall, the findings show that firm transparency is positively associated with employee-oriented CSP. Nevertheless, results obtained from breaking down the sample by company headquarter location and reporting regulation showed that this finding is valid only for European firms for which corporate social responsibility (CSR) reporting is mandatory.